Worm infestation among government school children in suklaphanta Municipality, Nepal. - Bhandari,Ganesh (2021)
Executive Summary: Background and Objective: In developing countries like Nepal, Intestinal worm infestation is one of the major childhood health problem causing gastrointestinal infections leading to morbidity and mortality among school going children. They are spread by faeco-oral route through contaminated sources and are associated with poor growth, reduced physical activity, impaired cognitive function, learning ability, nutritional deficiencies, particularly of iron and vitamin A. Although, these organisms may infect people of all ages but children are especially at risk because of their hand-mouth activity with high intensity in 3-12 year age group. Poverty, lack of awareness, failure to practice proper hand washing after defecation, unsafe drinking water and use of improper toilets are some important risk factors for worm infestation most of the parts in Nepal. The overall objective of the study was to identify the prevalence of worm infestation and anaemia and factors associated with worm infestation among government school children of Suklaphanta Municipality, Nepal. Methodology: A cross sectional study was conducted in 4 selected government school of Suklaphanta Munnicipality among students studying in grade 6,7 and 9. Data collection period was from November 2020 to Janaury 2021. Simple random sampling method was used for students selection and Convenient sampling technique for selection of schools.Considering prevalence of worm infestation of 60%, the calculated sample size was 401. Those students who were absent during data collection period were excluded from the study. Semi-structured questionnaires were used as a tool for data collection. Written permission was taken from each school‟s principal and parents and verbal consent as well as accent form was signed from each student. Then, the same number of plastic bottles were given for stool collection and collected the next day morning. Microscopic examination of stool was done by preparing slide using Normal Saline and Lugol's Iodine to observe the ova of different parasites. Then blood sample was withdrawn for hemoglobin estimation from each student to see the presence of anemia. All the collected data were entered in the Microsoft Excel 2007 and the data were analyzed using SPSS 16.0 version and the level of significance was set at 5%. Before starting the research, the proposal was ethically cleared by the Ethical review board of Nepal Health Research Council. Results: The mean age of the study with standard deviation was 13.62±1.24 years. The minimum age of participants was 12 and the maximum age was 17. The prevalence of worm infestation was 11.6 %. The highest prevalence was seen with Entamoeba Hystolytica(74.41 %) followed by Giardia Lambia (25.59%). Prevalence of worm infestation was found slight higher among male participants (11.8%) in this study than female (10.9%). Among various risk factors, those not taking anti helminthes drug during last 6 months, those having temporary type of toilet, not wearing footwear regularly, not washing hands regularly before meals and after going to toilet were 5,8,8,7,7 times respectively more risk for getting worm infestation and association was also statistically significant(p<0.000). Age, gender, ethnicity, educational status of father and mother did not show association with Worm Infestation. The prevalence of anemia worm infestation among male and female anemic participant was 13.7 % and 12.2 % respectively. Conclusion: Despite of government efforts, the worm infestation is still prevalent among school children as major public health problems which have negative consequences on cognitive function and learning ability. So, the Government of Nepal should co-ordinate with schools and municipalities to implement strategies like health awareness program, regular screening of worm infestation, compulsory use of anti-helminthes drug every 6 months, quality of safe drinking water supply and improvement of school sanitation so that there won‟t be no more burden of disease due to worm infestation in Nepal.